1998
DOI: 10.1183/09031936.98.12040770
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous laboratory-based comparison of ResMed Autoset with polysomnography in the diagnosis of sleep apnoea/hypopnoea syndrome

Abstract: ResMed Autoset (AS) is a simplified diagnosis system for obstructive sleep apnoea/hypopnoea syndrome (OSAS) based on the respiratory flow/time relationship by pressure variation measured through simple nasal prongs. A multicentre prospective trial was used to compare AS and polysomnography (PSG) for diagnosing 95 patients, with suspected OSAS. Physicians gave a pretest probability of the patient having OSAS. The apnoea/hypopnoea index (AHI) was compared between the two methods of diagnosis for the whole popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…13,20,21 This device has been tested in comparison with in-laboratory PSG and found to have a sensitivity of 92% and specificity of 79% in middle-aged patients for detection of sleep apnea. 20 All unattended studies were done within 2 mo before PSG; 99% were done within 1 day of PSG. The unit was delivered to the home and study participants were provided instruction and assistance regarding assembly on the night of the study.…”
Section: Home Sleep Studiesmentioning
confidence: 99%
“…13,20,21 This device has been tested in comparison with in-laboratory PSG and found to have a sensitivity of 92% and specificity of 79% in middle-aged patients for detection of sleep apnea. 20 All unattended studies were done within 2 mo before PSG; 99% were done within 1 day of PSG. The unit was delivered to the home and study participants were provided instruction and assistance regarding assembly on the night of the study.…”
Section: Home Sleep Studiesmentioning
confidence: 99%
“…Earlier studies reported strong correlations between the device-and polysomnography-measured respiratory indices, a tendency of autoCPAP to over-score events, and an underestimation of AHI at higher values [24][25][26]. These early studies were limited in that the devices were evaluated in diagnostic mode and autoCPAP devices are neither intended nor recommended for diagnostic purposes [10].…”
Section: Sleep-related Disordersmentioning
confidence: 99%
“…The AS is an auto-CPAP model in which the diagnostic mode allows the recording of different respiratory variables and patient's cardiac frequency. The system has been described and validated by several studies [17][18][19][20]. The AS provided a semi-quantitative reading of nasal ventilation.…”
Section: Sleep Studymentioning
confidence: 99%
“…First, the AS system does not allow quantification of the hours of sleep and it has not been validated in populations with a low pre-test probability of suffering obstructive sleep apnoea syndrome. In any case, the studies that have validated this technique versus polysomnography report that the AS system offers good correlation values in patients with a high AHI cut-off point, even with a low ESS score value, as is the case in the current population [18][19][20]. Secondly, a nonrandomised placebo controlled trial was used in an attempt to maximise the number of patients receiving effective CPAP treatment and exceeding the estimated sample size, as the percentage of patients with truly refractory AHT was small.…”
Section: Cpap Treatment In Dc-ht Ma Martínez-garcíamentioning
confidence: 99%